PENYULUHAN KESEHATAN TENTANG SISTEM PEMBIAYAAN DENGAN KUALITAS PELAYANAN KEPADA PASIEN RAWAT INAP - Iskandar Markus Sembiring; Novita Br Ginting Munthe; Sri Wulan; Rahmad Gurusinga; Beny Irawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Users of health services demand quality services in hospitals not only regarding recovery from physical illness but also regarding satisfaction with the attitudes, knowledge and skills of health workers in providing services and the availability of adequate facilities and infrastructure that can provide comfort. With the increasing quality of service, the function of services in hospitals needs to be improved so that they become more effective and efficient and provide satisfaction to patients and the community. The purpose of this health counseling is to provide a sense of calm and comfort to these class III inpatients with a financing system with quality inpatient services at the Sultan Sulaiman Regional General Hospital, Serdang Bedagai Regency in 2021. The results of this counseling show that out of 311 patients, 210 patients With the BPJS financing system, it is known that 143 people (46%) said the service quality was good and 67 people (21.5%) said it was not good. Of the 101 people with the general financing system, it is known that 59 people (19%) said the service quality was good and 42 people (13.5%) said it was not good. So it can be concluded that the quality of inpatient services at the Sultan Sulaiman Regional General Hospital, Serdang Bedagai Regency in 2021 is good.